Social media : the academic library perspective - Verishagen, Nina (Chandos social media series., 2019)
Social Media: The Academic Library Perspective provides a step-by-step guide on social media as written by somebody who has already done the work. Made up of case studies written by authors at various institutions who provide different perspectives on their institution's use of social media, the book highlights successes and failures, while also focusing on tips for social media management in the academic library that anybody in the community can interpret and adapt. Social media platforms are dealt with systematically, making this an essential guide for librarians who want to use social media to the benefit of their library.